The Development of Character-Education-Based Presentation Evaluation Tool on Indonesian as a General Education Courses Indonesia University of Education - Mochamad Whilky Rizkyanfi; Nuri Novianti Afidah (Journal of Language, Literature and Teaching, 2019)
The number of assignments for each course taken by students in one semester causes students to work their given assignments irresponsibly, without considering the assessment aspects required related to the assignment. One assignment that commonly done inattentively by the student is the presentation, and it applies to every course they have taken that requires a presentation. Based on the concept of eighteen values forming character education, the author compiles the concept of presentation assessment formats, including, discipline, hard work, creative, communicative, reading habit, and responsibilities in which are applied as a basis for assessment consideration adjusted to linguistic assessments. In this study, the authors used a qualitative approach. The authors highlighted that the eighteen values forming character could be adjusted in accordance with the Indonesian speaking skills assessment. Furthermore, the concept was then formulated into ten aspects of presentation evaluation, namely (1) language: formality, effectiveness, politeness; (2) material understanding: readiness, clarity, naturalness in answering questions; (3) slides: clarity, systematics; and (4) performance: politeness and style. This character-forming value can be well utilized as a guideline for presentation assessment formats implemented in a classroom. This tool will have a good impact that in line with the function of character education, which is to develop the basic potential to be kind, think well, and behave well; strengthen and build multicultural national behavior, and increase the sense of competitiveness nationally following in the world civilization.Keywords: presentation assessment, Indonesian Education presentation, character education